1997
DOI: 10.2307/1224092
|View full text |Cite
|
Sign up to set email alerts
|

On the evolutionary origins of the cacti

Abstract: On the evolutionary origins of the cacti. -Taxon 46: 217-232. 1997. -ISSN 0040-0262.Understanding evolutionary responses of plants to desert environments depends upon phylogenetic knowledge of desert plants. The diverse American desert family Cactaceae has been presumed, on the basis of distinctiveness, to be phylogenetically isolated and relatively ancient (> 65 million years old). Using maximum likelihood and parsimony analyses of the rapidly evolving internal transcribed spacer (ITS) sequences of nuclear ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
139
1
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(174 citation statements)
references
References 35 publications
14
139
1
8
Order By: Relevance
“…Taxa within the portulacaceous cohort have traditionally been treated at the rank of family; however, the degree of paraphyly in Portulacaceae suggests that phylogenetic resolution should be conceptually envisioned as an intrafamilial problem (Hershkovitz and Zimmer 1997). For example, in analyses of ITS, the genetic divergence of Cactaceae from Portulacaceae is equal to or less than that between many pairs of genera in Portulacaceae (Hershkovitz and Zimmer 1997).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Taxa within the portulacaceous cohort have traditionally been treated at the rank of family; however, the degree of paraphyly in Portulacaceae suggests that phylogenetic resolution should be conceptually envisioned as an intrafamilial problem (Hershkovitz and Zimmer 1997). For example, in analyses of ITS, the genetic divergence of Cactaceae from Portulacaceae is equal to or less than that between many pairs of genera in Portulacaceae (Hershkovitz and Zimmer 1997).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…The addition of molecular data has resulted in some clarification. In an analysis of ITS sequences, Hershkovitz and Zimmer (1997) suggested that Cactaceae were embedded within Portulacaceae and sister to Portulaca, Anacampseros, and relatives and portions of Talinum (the ACPT clade, from Anacampseroteae, Cactaceae, Portulaca, and Talinum; Nyffeler 2007). These findings were confirmed and extended by Applequist and Wallace (2001) in an analysis of ndhF sequences; Talinum with Talinella, Portulaca with Anacampseros, and the Cactaceae form three distinct lineages within a well-supported clade.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Hershkovitz (1993) associated Talinella with Portulacaria and Ceraria, sub sequent molecular studies have clearly shown that it is most closely related to Talinum Adans. (Hershkovitz & Zimmer 1997;Applequist & Wallace 2001). Gynodioecy has, however, also been reported in the monotypic Decaryia Choux, one o f the more basal lineages of the Otherwise dioecious Didiereaceae s.str.…”
Section: Taxonomic Significance Of Gynodioecy In Cerariamentioning
confidence: 99%
“…has been suggested (Rauh & Scholch 1965). Molecular evidence indicates that Ceraria and Portulacaria, as well as the African genus Calyptrotheca Gilg, are more closely related to Didiereaceae than to other Portulacaceae (Hershkovitz & Zimmer 1997;Applequist & Wallace 2000, 2001. The circumscription of Didiereaceae was therefore enlarged to accommodate these three genera (Applequist & Wallace 2003).…”
Section: Introductionmentioning
confidence: 99%